2003
DOI: 10.1080/00016350310007581
|View full text |Cite
|
Sign up to set email alerts
|

Caries‐preventive effect of fissure sealants: a systematic review

Abstract: The objectives of this study were to evaluate systematically the evidence of the caries-preventive effect of fissure sealing of occlusal tooth surfaces and to examine factors potentially modifying the effect. The search strategies included electronic databases, reference lists of articles, and selected textbooks. Inclusion criteria were randomized or quasi-randomized clinical trials or controlled clinical trials comparing fissure sealing with no treatment or another preventive treatment in children up to 14 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
133
0
20

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(156 citation statements)
references
References 25 publications
3
133
0
20
Order By: Relevance
“…Mejàre and Mjör (1990) recorded clinically extensive loss of 61% of low-viscosity glass ionomer sealants after 6-12 months, but all occlusal surfaces sealed with this material remained caries-free. No difference in dentine lesion development between the teeth sealed with a resin composite and those sealed with a lowviscosity glass-ionomer could be observed (Mejàre et al 2003). The same was observed for high-viscosity glass ionomers sealants.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Mejàre and Mjör (1990) recorded clinically extensive loss of 61% of low-viscosity glass ionomer sealants after 6-12 months, but all occlusal surfaces sealed with this material remained caries-free. No difference in dentine lesion development between the teeth sealed with a resin composite and those sealed with a lowviscosity glass-ionomer could be observed (Mejàre et al 2003). The same was observed for high-viscosity glass ionomers sealants.…”
Section: Discussionsupporting
confidence: 48%
“…Sealing caries prone pits and fissures is an effective approach for preventing carious lesion development (Ahovuo-Saloranta et al 2008). In this aspect, resin based and low viscosity glass ionomer sealants have been extensively studied showing promising results (Mejàre et al 2003;Beiruti et al 2006;Chen et al 2012). However, the ability to perform sealants using ART technique seems to be highly dependent of sufficient practical skills and it might limit a wider implementation of this approach in oral health care services.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative to allow a more efficient biofilm control in this area is the use of dental sealants. 43 The sealing of occlusal surfaces in a preventive approach has shown positive results (caries risk reduction of 33-65%); [44][45][46][47][48] however, it will depend on a series of variables. Ahovuo-Saloranta et al, 48 through a systematic review of the literature, showed that the effectiveness of sealants is obvious for high caries-risk individuals, but information on the benefits of sealing to patients with different caries-risk levels is lacking.…”
Section: Biofilm Control and Heath Promotionmentioning
confidence: 99%
“…The material used to seal the surface is also an important factor, and resinbased sealants are preferable when compared to glass ionomer cement. 45 Loss or fracture of sealants should be considered, since a significant relation has been established between intact sealants and a reduction in caries risk. 45 There is evidence indicating that a much better effect is observed if re-sealing is performed.…”
Section: Biofilm Control and Heath Promotionmentioning
confidence: 99%
“…This recommendation is adopted by most of clinical guidelines for caries prevention in pre-school children. [2][3][4] On the other hand, recent systematic reviews 5,6 have found insufficient evidence to support the use of GI sealants. The present study helps to fill the gap in the evidence in this respect.…”
Section: Commentarymentioning
confidence: 99%